Integration of Islamic Values in Secondary School Curriculum: A Case Study in Public Schools - Jumahir, Jumahir; Ahmad, Mukhtar Muhammad Mahdar; Aimang, Hasrat A (Journal Evaluation in Education (JEE), 2026)
Purpose of the study: This study aims to describe and analyze how Islamic values are integrated into the curriculum at public junior high schools in the Luwuk sub-district, and to identify the supporting and inhibiting factors in their implementation. Methodology: This research employs a qualitative case study approach. Data were collected through in-depth interviews with teachers and school principals, direct classroom observations, and analysis of curriculum documents and syllabi. Data were analyzed descriptively through data reduction, presentation, and conclusion drawing. Main Findings: The findings reveal that the integration of Islamic values is carried out implicitly through character strengthening, habituation programs, and contextual approaches across various subjects. Although not all schools apply this integration systematically, educators consistently strive to instill values such as honesty, responsibility, and tolerance. Key supporting factors include teachers' commitment and the reinforcement of school culture, while the main challenges involve limited training opportunities and the absence of standardized curriculum guidelines. Novelty/Originality of this study: This study offers new insights into the practice of integrating Islamic values into formal education at the junior high school level, focusing on local-level factors influencing its implementation. It also highlights the importance of empowering teachers and formulating clearer curricular policies to support the successful integration of these values.